The role of unification in explanations of facts - Weber, Erik; Van Bouwel, Jeroen; Lefevere, Merel (EPSA Philosophy of Science 2009, 2012)
In the literature on scientific explanation, there is a classical distinction between explanations of facts and explanations of laws. This paper is about explanations of facts. Our aim is to analyse the role of unification in explanations of this kind. We discuss five positions with respect to this role, argue for two of them and refute the three others.